2015
DOI: 10.1111/mcn.12169
|View full text |Cite
|
Sign up to set email alerts
|

Bangladeshi women's experiences of infant feeding in the London Borough of Tower Hamlets

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
4
12
0
1
Order By: Relevance
“…Findings on the cultural barriers to promotion of breastfeeding and healthy weight gain in children and infants are consistent with that in previous literature, including: pressure to fully or partially replace breastfeeding with infant formula [37,[50][51][52][53][54]; use of formula to encourage infant sleeping, feeding by other family members or reduce infant crying [36,37,50,51,[55][56][57][58]; beliefs that large infants signi ed health, especially from countries where infants at are risk of malnutrition and undernutrition [36,50,52,[57][58][59][60][61][62][63]; limited access to support from nurses and midwives for infant feeding and care [54,55,64,65]; and introduction of solid foods before 4-6 months [33,56,66], across South Asian, East Asian, Middle Eastern, African, Maori, Paci c Islander and Indigenous Australian populations and peoples migrating to overseas countries. Speci c cultural beliefs were also identi ed, such as forceful infant feeding for weight gain by Bangladeshi parents, from fear that inadequate nutrition would result in child sickness or death [59,67,68], or norms where playing with children may not be common practice [69,70].…”
Section: Discussionsupporting
confidence: 85%
“…Findings on the cultural barriers to promotion of breastfeeding and healthy weight gain in children and infants are consistent with that in previous literature, including: pressure to fully or partially replace breastfeeding with infant formula [37,[50][51][52][53][54]; use of formula to encourage infant sleeping, feeding by other family members or reduce infant crying [36,37,50,51,[55][56][57][58]; beliefs that large infants signi ed health, especially from countries where infants at are risk of malnutrition and undernutrition [36,50,52,[57][58][59][60][61][62][63]; limited access to support from nurses and midwives for infant feeding and care [54,55,64,65]; and introduction of solid foods before 4-6 months [33,56,66], across South Asian, East Asian, Middle Eastern, African, Maori, Paci c Islander and Indigenous Australian populations and peoples migrating to overseas countries. Speci c cultural beliefs were also identi ed, such as forceful infant feeding for weight gain by Bangladeshi parents, from fear that inadequate nutrition would result in child sickness or death [59,67,68], or norms where playing with children may not be common practice [69,70].…”
Section: Discussionsupporting
confidence: 85%
“…The complementary feeding practices of Bangladeshi parents in the UK are complex, since many factors influence the changes of an ethnic group's dietary habits including acculturation, food availability, convenience, and income, all of which may contribute to the susceptibility for the development of various chronic diseases in adulthood [19]. Consequently, the feeding practices of British Bangladeshi children and adults alike in Tower Hamlets are regularly influenced by the UK society, the London Bengali community, and the Bangladeshi culture alike [20].…”
Section: Introductionmentioning
confidence: 99%
“…The three Children’s Centre groups existed previously to the project and the project team ensured that the discussions were planned in a time and place when the women were already meeting. Our previous experience of engaging women from communities across Britain [ 1 , 21 , 22 ] had shown that it was often impractical to ask women with small babies to attend an extra group meeting at a particular time of day. In contrast, visiting existing baby drop-in groups was significantly more successful as women were used to attending these groups at regular intervals and were also in a setting where they felt comfortable.…”
Section: Methodsmentioning
confidence: 99%
“…We knew from previous research with the Bangladeshi community in East London that women in that community preferred to engage with healthcare professionals through face-to-face discussions rather than written materials [ 21 ] and this kind of community intelligence was crucial to guiding our approach for this project. In addition, group discussions allow the conversation to flow, without a specific agenda.…”
Section: Methodsmentioning
confidence: 99%